2021
DOI: 10.3390/ijerph181910258
|View full text |Cite
|
Sign up to set email alerts
|

How Can Flowers and Their Colors Promote Individuals’ Physiological and Psychological States during the COVID-19 Lockdown?

Abstract: The global spread of COVID-19 has disrupted the normality of people’s daily lives, leading the population to social distancing and isolation. The closure of green areas also affected the well-being of the individual during the COVID-19 pandemic. Viewing flowers is expected to have similar positive effects to viewing natural scenery. Therefore, this study investigates how white, red, and yellow flower colors affect individuals’ psychological and physiological well-being. The experiment was conducted in an offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 64 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…Thus if a landscape architect was restricted to the use of a single flower colour within a therapeutic environment, white would be the colour to recommend. This contradicts Xie et al (2021) who found white flowers reduced cheerfulness and relaxation compared to red or yellow flowers. The reason for this is not clear, but may relate to different visual stimulations (cut roses arranged in glass vases) or cultural context (participants based in China).…”
Section: Preference In Relation To Moodmentioning
confidence: 66%
See 1 more Smart Citation
“…Thus if a landscape architect was restricted to the use of a single flower colour within a therapeutic environment, white would be the colour to recommend. This contradicts Xie et al (2021) who found white flowers reduced cheerfulness and relaxation compared to red or yellow flowers. The reason for this is not clear, but may relate to different visual stimulations (cut roses arranged in glass vases) or cultural context (participants based in China).…”
Section: Preference In Relation To Moodmentioning
confidence: 66%
“…Questionnaires using photographs have been used before to elicit responses to flower colour (Li et al, 2012;Hůla and Flegr, 2016;Neale et al, 2021), and whilst this approach does not immerse the participant in the landscape in the way that an in vivo experiment would, it can still be used to determine preferences as well as emotional and physiological responses (Jo et al, 2019). Photographs can also indicate or imply 'mass plantings', more akin to an in vivo landscape than perhaps individual flowers or pots of flowers displayed in a laboratory can (Jang et al, 2014;Xie et al, 2021). A photo-based questionnaire has the added advantage of allowing for a greater number of participants over a given time, and thus aid statistical robustness.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the plant's colour can aid people in relieving stress and enhancing their emotional condition (Jang et al, 2014). In line with these findings, Xie et al (2021) also proposed that seeing flowers bloom can have physiological and psychological advantages such as reduced stress and increased well-being. The colour of the flower also has a favourable influence on the individual's physiology and psychology.…”
Section: Recommendationmentioning
confidence: 81%
“…The questionnaire for landscape perception evaluation is shown in Table 3 . The evaluative dimension includes spatial characteristics, environment greening, and psychological perception, and an 11-class linear scale is used for conversion ( 38 , 39 ).…”
Section: Methodsmentioning
confidence: 99%